The Association Between Maternal Age at Childbirth and Child Nutritional Outcomes: A Cross-sectional Study From Serbian Roma Communities - Jelena Čvorović PhD (SAGE Publishing, 2024)
Objectives. Extremes of maternal age at childbirth may influence child nutritional outcomes, but this is under-researched in Roma populations. Methods. The study was a secondary data analysis of Multiple Indicator Cluster Surveys for Serbian Roma settlements and included 2564 children aged 0 to 59 months. Results. About 19% of children were stunted, 9% underweight, 16% were unwanted and born with a low birth weight. Logistic and linear regressions show that maternal age at childbirth had no association with either nutritional or growth outcomes of Roma children ( P  > .05). Instead, child characteristics: being born as a boy, low birth weight, unwanted, younger age, and maternal characteristics: short birth spacing, higher parity and low socioeconomic status were associated with children's malnutrition. Conclusion. Maternal age at childbirth per se does not increase the chances of poor child health outcomes, as the risks seem to be related more to individual child and maternal characteristics and maternal behavioral patterns.